Nivolumab for the treatment of urothelial cancers. Issue 3 (4th March 2018) - Teo, Min Yuen; Rosenberg, Jonathan E.
ABSTRACT: Introduction : Advanced urothelial cancer patients had limited therapeutic options following failure of platinum-based chemotherapy. The recognition that anti-PD1/PDL1 immune checkpoint inhibitors lead to dramatic and durable responses in a subset of patients has transformed the therapeutic landscape of these cancers. Since May 2016, five agents targeting this pathway have been approved by the US FDA, including the PD-1 inhibitor nivolumab. Areas covered : The purpose of this paper was to review the safety, activity and efficacy of nivolumab, an anti-PD1 checkpoint inhibitor for the treatment of locally-advanced or metastatic urothelial cancers. Future therapeutic perspectives were also discussed. Expert commentary : Nivolumab is one of five anti-PD1/PDL1 checkpoint inhibitors approved for treatment of advanced urothelial cancers. While durable responses can be observed, only 15 – 24% of patients are likely to respond. To date, there are no validated biomarkers, including PDL1 expression, which might accurately identify patients who are likely to respond. Many different biomarkers are currently under active investigation. Future direction for therapeutic development is likely to involve combination therapies with PD1/PDL1 agent as the therapeutic backbone.